Effect of Processing Additives on Organic Photovoltaics: Recent Progress and Future Prospects. Issue 10 (7th October 2016) - Kwon, Sooncheol; Kang, Hongkyu; Lee, Jong‐Hoon; Lee, Jinho; Hong, Soonil; Kim, Heejoo; Lee, Kwanghee
Abstract : Due to the short diffusion length of approximately 10 nm of an exciton in bulk heterojunction (BHJ) organic solar cells (OSCs) comprising electron donors and acceptors, a formation with well phase‐separated nanomorphology in BHJ films has been one of the most important issues in achieving efficient charge separation and extraction in OSCs. By adding a small amount of a high boiling point solvent or molecules to a bulk heterojunction (BHJ) solution, processing additive techniques have recently begun to offer an attractive and efficient method for controlling the nanoscale BHJ morphology of state‐of‐the‐art OSCs with power conversion efficiencies (PCEs) exceeding approximately 11%. However, it remains unknown whether the effect of processing additives can potentially pave the way for the ongoing development of various BHJ components and the commercialization of OSCs. Here, recent progress in understanding and developing the effects of processing additives on OSCs is highlighted. This overview suggests possible guidelines for a wide range of BHJ components with respect to morphological/structural evolution. Furthermore, the rational correlations among processing additives, BHJ components, and fabrication technologies and the performance of high‐performance and low‐cost OSCs are discussed along with future commercialization prospects. Abstract : For efficient charge separation and extraction in a device, the specific characteristics of processing additives, such as high boiling points and selective solubility, provide a special opportunity to form a well phase‐separated nanomorphology in a bulk‐heterojunction (BHJ) film. The applications of processing additives to commercial OPVs can be further developed with respect to future demands for various BHJ materials, such as high performance, long‐term stability and eco‐friendly fabrication.